Comparison of Learning Achievement in Science Subject on the Topic Force in Daily Life of Grande 5 Students at the Demonstration School of Suan Sunandha Rajabhat University Using Practical Package and Traditional Teaching - Camhongsa, nungrutai; Jetsadawiroj, Siripat (SSRU Academic Journal of Education, 2024)
The aims of this research were 1) to develop and study the effectiveness of the practical package topic force in daily life on the standardized efficiency criteria of 80/80; 2) to compare learning achievement in science subject in topic force in the daily life of grade 5 students by using the practical package and traditional teaching; and 3) to study the satisfaction of grade 5 students toward the practical package in topic force in daily life. The samples were grade 5 students in the second-semester academic year 2022 at the demonstration school of Suan Sunandha Rajabhat University by cluster random sampling.The instruments used for this study included 1) the practical package topic force in daily life 2) the Science lesson plan with the practical package topic force in daily life 3) The achievement test 4) Satisfaction rating. The statistics used in the research were mean (), standard deviation (SD.), determination of the efficiency E1/E2, and hypothesis testing using t-test (Pair). The results of the research found that 1) The efficiency of the practical package topic force in daily life for grade 5 students was 81.25/81.56 which was higher than the efficiency criterion of 80/80; 2) The academic achievement of students who learned through the practical package topic force in daily life was higher than those who learned through traditional teaching at the statistical significant .05; and 3) The satisfaction of grade 5 students toward the practical package in science subject topic “force in daily life” were at a high positive level